2010
DOI: 10.1094/fg-2010-0914-01-rs
|View full text |Cite
|
Sign up to set email alerts
|

Herbage Nutritive Value of Tall Fescue Fertilized with Broiler Litter and Inorganic Fertilizer

Abstract: The nutrients in broiler litter can replace inorganic fertilizer additions, but must be managed to minimize soil nutrient build‐up and off‐site losses in the environment. Herbage dry matter (DM) and nutritive value were measured in tall fescue at litter rates of 0, 4.5, 9.0, 13.5, and 18.0 Mg/ha/year, as compared to inorganic fertilizer (INORG) that provided N, P2O5, and K2O (224‐112‐224 kg/ha/year), in soil with no litter history. The treatments were split‐applied in autumn and spring, and forage was harveste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The use of broiler litter (a mixture of manure, wasted feed and bedding material) as fertilizer represents an opportunity to produce high‐quality forage for livestock, reduce potential nutrient loss to the environment and remove nutrients added by the manure through hay production (Read et al ., ). Tall fescue [ Lolium arundinaceum (Schreb.)…”
Section: Introductionmentioning
confidence: 97%
“…The use of broiler litter (a mixture of manure, wasted feed and bedding material) as fertilizer represents an opportunity to produce high‐quality forage for livestock, reduce potential nutrient loss to the environment and remove nutrients added by the manure through hay production (Read et al ., ). Tall fescue [ Lolium arundinaceum (Schreb.)…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, Pitman (1999) conducted a 3‐yr study in Georgia on mixed swards of cultivar Georgia 5 tall fescue and common bermudagrass and reported DM yields in March and May were greater when a split application of 150 kg N ha −1 was limited to the cool‐season grass, as compared to the warm‐season grass. In a Mississippi study on the response of Jesup MaxQ to five litter rates (0–18 Mg ha −1 , as‐is basis) applied in April, Read et al (2010) reported significant linear increases in DM yield, from approximately 0.3 to 2.3 Mg ha −1 , and in crude protein concentration, from 67 to 127 g kg −1 , at the mid‐season harvests in either May (2006) or June (2007). They suggested this response was due to N mineralization during the 30‐d period between application and the mid‐season harvest, which is consistent with evidence of relatively rapid release of inorganic N from broiler litter into the surface soil up to 28 d post‐application (Sistani et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…While cool‐season favored tall fescue, the Mississippi Nutrient Management Code 590 requires that, among other considerations, the manure applications in autumn and winter be done when the crop is actively growing on unsaturated soil, and this management option is addressed specifically in an approved nutrient management plan (Mississippi Natural Resources Conservation Service, 2013). The condition of growth activity on an essentially continual basis is met in a cool‐season/bermudagrass production system, and knowledge of yield improvement in response to seasonal N fertilization has potential to enhance the fertilizer value of poultry litter (Newton et al, 2003; Read et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations